CO2 absorption into loaded aqueous MEA solutions: Kinetics assessment using penetration theory. (October 2016) - Putta, Koteswara Rao; Pinto, Diego D.D.; Svendsen, Hallvard F.; Knuutila, Hanna K.
Highlights: Concentration based and activity based kinetic models are developed based on penetration theory. The developed models are validated using published experimental data from three different apparatuses. The new models predict desorption rates in addition to absorption rates without any modifications. Activity based kinetic model predicts with absorption rates for MEA solutions outside the fitted concentration rage also with good accuracy. The models can be used for cases with and without gas phase mass transfer resistance. Abstract: Improved kinetic models based on penetration theory for CO2 capture process by aqueous Monoethanolamine (MEA) solution are developed within MATLAB software in this study. Base contributions of major bases MEA and H2 O present in the solution are considered in the carbamate formation reaction and termolecular reaction mechanism is used for carbamate formation. Both concentration based and activity based kinetic models are valid over the temperature range of 293–343 K, CO2 loading range of 0–0.5. The concentration based kinetic model is valid for MEA concentrations up to 5 M and activity based kinetic model is valid up to 9 M MEA. The developed kinetic models are validated with experimental absorption data from strings of discs, wetted wall column and laminar jet absorber. Both models predict absorption rates as well as desorption rates with good accuracy.